Model Matematika Rantai Makanan Mangsa-Pemangsa Tiga Spesies dengan Adanya Ketakutan pada Mangsa dan Predator Perantara - Arsya, Nadila; Subhan, Muhammad (UNIVERSITAS NEGERI PADANG, 2024)
A three-species prey-predator interaction is an interaction involving three species, namely the prey species, the intermediate predator and the top predator. The presence of predators can cause fear in their prey. This research aims to determine the local stability analysis of the mathematical model of the prey-prey food chain for three species in the presence of fear of intermediate prey and predators. This research is also equipped with numerical simulations that show the effects of fear on prey and intermediate predators. Based on the analysis that has been carried out, four fixed points have been obtained with their respective stability. Numerical simulations from the model show that when there is no fear of intermediate prey and predators, the population of each species shows irregular oscillations, whereas in the presence of fear of intermediate prey and predators the population stabilizes towards a fixed point . However, if the level of fear is too high for prey or intermediate predators, it will cause the population of top predators to become extinct.